Awareness about Consumer Protection Act amongst Patients Visiting a Private Medical College and Hospital at Chennai: A Descriptive Study - P Shruthi; Uma Maheshwari (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: To assess the knowledge regarding Consumer Protection Act amongst patients visiting a tertiarycare hospital at Chennai.Methodology: A cross-sectional descriptive questionnaire based survey was carried out on 550 patientsvisiting a private medical college and hospital at Chennai and the data was collected. The interview consistingof closed ended questions on CPA. Statistical analysis was done using appropriate statistical tools in SPSSsoftware.Observation and Results: Young male respondents were found to have more awareness in comparisonwith females. Education and monthly income were found to have positive association with the level ofawareness.62% of the study participants have heard about CPA. In cases of medical negligence, 78%participants would visit police station rather than a consumer redressal forum.80% of the participants wereunaware of the location of consumer court. Approximately half of the respondents (45%) felt that medicalservices by doctors were liable for punishment under CPA in case of negligence.Conclusion: Knowledge of what may influence patients is of utmost importance in cases of meeting theirexpectations and demands. Although the Consumer protection Act empowers patients to demand qualitycare, still complaints against medical professionals for errors, unfair access and poor satisfaction inservice rendered remains. Hence awareness of patients rights and legislations would pave a path towardsimprovement in the quality of medical service rendered , thereby providing satisfaction to both patients andhealth care provider.